Imagining the World with NoReligion - Mayasari, Nuki (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
Segregations caused by religions may diversely be responded by a group of people. Being partly perceived as a subject for conducting dialogue, religion may also be considered as a segregating factor that shall better be diminished. Religion, for some groups of people, tends also to be seen as contradictory to the nature of science and toleration. To this extent, the notion of engaging the segregated groups of people can also be related to the concept of Asutosh Varshney in terms of promoting civic engagement through social media with a different setting. Although the movement is virtual community based, the promotion of NoReligion is also intended for giving another view in the state realm.Keywords: NoReligion, atheism, engagement, segregation, dismissal of religion